Contrasting Roles of Mannan-Specific Monoclonal Immunoglobulin M Antibodies in the Activation of Classical and Alternative Pathways by Candida albicans - Zhang, Mason X. (American Society for Microbiology, 1998)
Polyclonal antimannan immunoglobulin G (IgG) activates the classical complement pathway and accelerates initiation of the alternative pathway by Canidida albicans. This dual role was assessed for two antimannan IgM monoclonal antibodies (MAbs). MAb B6.1 is specific for an epitope on the acid-labile portion of C. albicans phosphomannan; MAb B6 is specific for an epitope on the acid-stable region. Both MAbs were potent activators of the classical pathway but poor facilitators of alternative pathway initiation.